Sistem Pendukung Keputusan Menentukan Diskon Biaya Perawatan Rumah Sakit Deli Menggunakan Metode TOPSIS - Didi Prawira Suprayogi; Muhammad Syahrizal (STMIK Budi Darma, 2020)
Decision support system is a computer-based system that functions for decision making by utilizing data and models to solve unstructured and semi-structured problems within a company or organization. Deli Medan Hospital is one hospital that offers quality health services accompanied by competitive prices. The price offered by Deli Medan Hospital is in accordance with the quality of delivery provided so that the use of this hospital's health services is always a satisfaction. this can be seen from the number of patients who are still increasing every year Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) is one of the multicriteria decision making methods first introduced by Yoon and Hwang (1981). TOPSIS uses the principle that the chosen alternative must have the closest distance from the positive ideal solution and the farthest from the negative ideal solution from a geometric point of view using Euclidean distance to determine the relative proximity of an alternative to the optimal solution. Positive ideal solutions are defined as the sum of all the best values that can be achieved for each attribute, while the negative-ideal solution consists of all the worst values achieved for each attribute